Mendel Lectures 2002-2022 - Hobzová, Dominika; Krejčí, Kateřina; Krejčí, Lumír; Mizerová, Alena; Relichová, Jiřina; Pavlíková, Gabriela (Mendel Lectures, 2022)
Title in English: Mendel Lectures 2002-2022 This jubilee publication provides a representative overview of twenty years of the world-renowned lecture series and introduces all the speakers - more than 130 scientists, including 15 Nobel Prize laureates. The book details the history of the Mendel Lectures and the significant activity of scientists associated with the so-called "Brno Initiative": Kim A. Nasmyth, Anna Nasmyth, Max Perutz, Paul Nurse, Tim Hunt, James Watson, Eric Wieschaus, Peter Swetly, Jiřina Relichová, Jan Motlík, Emil Paleček, Eva Jiřičná, and Gustav Ammerer - the founders of the series, thanks to whom the lectures regularly take place on the premises, moreover, where the founder of genetics worked 200 years ago.